Psychological outcomes and associated factors amongst healthcare workers during a single wave, deeper into the COVID-19 pandemic in China - Tang, Jianyong; Wu, You; Qi, Hongyan; Li, Dongjing; Shi, Jianfei; Wang, Wei; Niu, Mengmeng; Liu, Liang; Wang, Dong; Li, Xia (Frontiers in Psychiatry, 2022)
Background To date, the repeated breakout of the novel coronavirus disease 2019 (COVID-19) pandemic across many regions in China has caused continuous physical and mental harm to health care workers. This study investigates the psychological burden of the pandemic and its associated risk factors among Chinese healthcare workers (HCWs) during a single wave of COVID-19. Methods For this cross-sectional web-based survey conducted from January 16, 2022 to February 5, 2022, a total of 412 HCWs from Northwestern China were recruited. Their socio-demographic data and COVID-19 related survey variables were then collected using online self-rating questionnaires. In addition, the Chinese versions of well-validated instruments, including the 12-item General Health Questionnaire for psychiatric morbidity, the Generalized Anxiety Disorder Scale-7 for anxiety, the Patient Health Questionnaire-9 for depression and the Insomnia Severity Index-7 for insomnia, were used to assess the participants' mental health status. Multivariate logistic regression analysis was eventually performed to identify the risk factors associated with the psychological outcomes. Results Of the 388 participants who were included in the final study (94.17% response rate), the prevalence of anxiety, depression, and insomnia symptoms were 25.3% (95% CI: 20.9-29.6%), 40.7% (95% CI: 35.8-45.6%), and 30.9% (95% CI: 26.3-35.5%), respectively. Multivariate logistic regression analysis revealed that being a woman and having a perceived need for psychological support were risk factors for all psychological outcomes, while poor disease cognition and perceived susceptibility were risk factors for anxiety. Poor disease cognition and being unvaccinated against COVID-19 were risk factors for depression, with the latter also being an independent risk factor for insomnia. Conclusion This study has identified a relatively lower prevalence rate of psychological disorders among Chinese HCWs during a single wave, deeper into the COVID-19 pandemic. Female HCWs, and those who had a perceived need for psychological support, had poor disease cognition, were perceived as susceptible to COVID-19 and had not been vaccinated against COVID-19 deserve more attention.